Trump's assault on foreign aid: Implications for international development cooperation - Sebastian Haug; Anna Novoselova; Stephan Klingebiel (German Institute of Development and Sustainability (IDOS), 2025)
The United States of America has long been a leading force in international development cooperation, both politically and financially. However, the first weeks of the second Trump administration have called the traditional role of US foreign aid fundamentally into question. From a 90-day funding freeze to the withdrawal from United Nations (UN) bodies and the dismantling of the US Agency for International Development (USAID), measures taken by Trump and his team are not only having palpable repercussions on a wide range of humanitarian and development programmes, but they also point to more far-reaching implications. Against this backdrop, this paper presents the contours and discusses the global consequences of Trump's assault on US foreign aid, as of late February 2025. We outline the extant role of the United States as a donor in Section 2 and review the changes announced - and/or implemented - by the current US government in Section 3. Section 4 discusses the implications of US funding cuts for bilateral cooperation, while Section 5 focuses on repercussions on multilateral development work. Section 6 outlines three scenarios on how the ongoing changes in the United States might affect the field of international development. We discuss the possible ramifications of (a) a revamped US approach to foreign aid centring on crude national interests, (b) a US retreat that is at least partially offset by other providers and (c) a US retreat without other providers stepping in. Section 7 concludes by discussing the implications for dealing with the second Trump administration. We outline four recommendations that address stakeholders across the - increasingly outdated - donor-recipient divide: (1) refining development cooperation approaches, (2) strengthening the multilateral development system, (3) promoting Southern self-reliance and (4) fostering alliances beyond a Trump-led US government.
Keywords: 320; USA; USAID; foreign aid; development cooperation; development policy; Donald Trump; United Nations; multilateralism